2014
DOI: 10.4137/cpath.s13580
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological Aspects of Hashimoto's Thyroiditis: Our Experience at a Tertiary Center

Abstract: INTRODUCTIONHashimoto’s thyroiditis is the most common form of acquired hypothyroidism. Fine needle aspiration cytology is one important tool in diagnosing Hashimoto’s thyroditis, along with clinical, biochemical, immunological and ultrasonographical modalities. The present study examines cytological aspects of Hashimoto’s thyroiditis along with their correlation with clinical, biochemical and immunological findings, whenever available.MATERIALS AND METHODSThis is a retrospective study of 50 cases of Hashimoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
5
14
1
Order By: Relevance
“…Fire flares were noted in few patients of HT ( n = 3). Similar frequency was noted by Rathi et al [ 29 ]. In contrast, some studies noted slightly more frequency [ 26 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…Fire flares were noted in few patients of HT ( n = 3). Similar frequency was noted by Rathi et al [ 29 ]. In contrast, some studies noted slightly more frequency [ 26 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…Monika Rathi et al and Friedman M et al also reported markedly high percentage of cases showing Hurthle cell change. 14,15 Data in this study on follicular atypia 26.66% and follicular cell infilteration by lymphocytes 82.66% were comparable with the study of Jayaram et al 16 CONCLUSION: FNAC is a safe, reliable, cost effective and time saving method in the diagnosis of thyroiditis. Being a benign condition also reduce the rate of unnecessary operation, which can be treated conservatively.…”
Section: Introductionsupporting
confidence: 76%
“…About little more than 12% of the subjects were found to be euthyroid (Rathi M et al). 23 The cytological compensatory changes that was suggestive of hypothyroid state. Fluoride that is absorbed in to the blood is found in higher concentration in the plasma than the cells around.…”
Section: Discussionmentioning
confidence: 99%